1976
DOI: 10.1152/jn.1976.39.6.1334
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative studies of single-cell properties in monkey striate cortex. III. Spatial frequency

Abstract: 1. The response properties of single cells in monkey striate cortex were examined using moving bars, square-wave gratings, and sine-wave gratings. 2. The moving of cells studied were not selective for bar width or for the spatial frequency of square-wave gratings. 3. Most cells responded selectively to the spatial frequency of the sine-wave gratings. 4. The spatial frequency of the sine-wave grating eliciting the optimal response could not be predicted from the organization of the receptive field of each cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
112
2
2

Year Published

1980
1980
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(137 citation statements)
references
References 3 publications
19
112
2
2
Order By: Relevance
“…These tuning characteristics are similar to those reported in studies of area V1 using flashed or drifting gratings (14,15).…”
Section: Resultssupporting
confidence: 85%
“…These tuning characteristics are similar to those reported in studies of area V1 using flashed or drifting gratings (14,15).…”
Section: Resultssupporting
confidence: 85%
“…More generally, this type of cell, which we call bar cells in the following, respond most strongly to single bars and their responses decrease with the addition of further parallel bars to make a grating. In previous studies Schiller et al (1976) also found many cells in area V1 which responded strongly to single bars and edges but did not respond to sine-wave gratings. Blakemore and Tobin (1972) measured the response of a 'complex' cell to a white bar of optimal orientation, position and size in the presence of a bar grating covering the area outside a circle which was somewhat larger than the region in which the cell responded to the bar stimulus.…”
Section: Introductionmentioning
confidence: 77%
“…The plausibility of this extension can be tested by measuring the response of single-bar cells of the type described by Schiller et al (1976) and von der Heydt et al (1992) as a function of both the width of the bars and the (fundamental) frequency of the bar grating. The computational model proposed above concerns the process of conveying or not conveying the activities of simple and complex cells to higher stages.…”
Section: Computational Model Of Bar Cellsmentioning
confidence: 99%
“…Figure 9 demonstrates the spatial specificity of BOLD by exploiting the non-uniform distribution of directionally selective cells across the layers of the striate cortex. About one-third of the striate cells are known to be directionally selective (Goldberg & Wurtz 1972;Schiller et al 1976;De Valois et al 1982;Albright 1984;Colby et al 1993). However, these cells do not exhibit a uniform laminar distribution.…”
Section: (Iii) Spatial Specificity Of Bold Fmrimentioning
confidence: 99%